2017
DOI: 10.1111/nyas.13312
|View full text |Cite
|
Sign up to set email alerts
|

Can pulses play a role in improving cardiometabolic health? Evidence from systematic reviews and meta‐analyses

Abstract: Obesity, diabetes, and cardiovascular disease (CVD) present important unmet prevention and treatment challenges. Dietary pulses are sustainable, affordable, and nutrient‐dense foods that have shown a wide range of health benefits in the prevention and management of these conditions. Despite these findings, recommendations for pulse intake continue to vary across chronic disease guidelines, and intake levels continue to remain low. Here, we summarize findings from recent systematic reviews and meta‐analyses ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 113 publications
5
72
0
5
Order By: Relevance
“…Studies have shown that regular consumption of pulses provides multiple health benefits and is associated with reduced cardiometabolic risk factors (22,29), and these findings are supported by a recent study summarizing systematic reviews and meta-analyses (39). Despite these findings, however, the consumption of pulses in developed countries remains low, with 20 and 8% of the population regularly consuming pulses in Canada and the United States, respectively (20,28).…”
supporting
confidence: 50%
“…Studies have shown that regular consumption of pulses provides multiple health benefits and is associated with reduced cardiometabolic risk factors (22,29), and these findings are supported by a recent study summarizing systematic reviews and meta-analyses (39). Despite these findings, however, the consumption of pulses in developed countries remains low, with 20 and 8% of the population regularly consuming pulses in Canada and the United States, respectively (20,28).…”
supporting
confidence: 50%
“…Pulse consumption has been associated with positive health outcomes across multiple populations (Viguiliouk, Blanco Mejia, Kendall, & Sievenpiper, 2017). Consumption of chickpeas, which are commonly available pulses worldwide, has been proposed to be beneficial in the managing of multiple chronic diseases such as cardiovascular diseases and obesity (Gupta et al, 2017;Padhi & Ramdath, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses investigating the effects of nut consumption reported reductions in TC, LDL-C, TAG, diastolic blood pressure, FG and glycosylated Hb (both in T2D patients) (86)(87)(88) , but no effects on body weight, HDL-C, SBP and C-reactive protein (87,89,90) . Focusing on legumes, one meta-analysis of ten RCT indicated that interventions to increase the intake of legumes were associated with decreased TC and LDL-C levels compared with a control group (91) , others reported reductions in C-reactive protein, SBP and FG (92,93) , but no effects on body weight (92) . Evidence from meta-analyses of intervention trials showed that higher consumption of sugar-sweetened beverages (SSB) leads to a considerable increase in body weight (94,95) .…”
Section: Meta-analyses Of Randomised Controlled Trialsmentioning
confidence: 99%